1988
DOI: 10.1099/0022-1317-69-8-2043
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Sequence Analysis of the Mumps Virus Gene Encoding the P Protein: Mumps Virus P Gene Is Monocistronic

Abstract: SUMMARYThe nucleotide sequence of the P (phosphoprotein) gene of two strains of mumps virus has been determined from overlapping cDNA clones. The P gene contained a single open reading frame coding for a protein of 391 amino acids with a calculated Mr of 41587, in good agreement with the value (40K to 45K) estimated from electrophoretic mobility on SDS-polyacrylamide gels. No open reading frame analogous to the C gene of other paramyxoviruses existed in the mumps virus P gene region. Comparison of the amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Early peptide mapping data obtained for the P and "C-like" proteins of two other paramyxoviruses, Newcastle disease virus (NDV) and mumps virus, suggested that both proteins are encoded by the same reading frame (Collins et al, 1982;Herrler and Compans, 1982). Recently the NDV and mumps virus P genes have been sequenced and found to contain one open reading frame (Sato et al, 1987;McGinnes et al, 1988;Takeuchi et al, 1988) from which it has been suggested that both the P and "C-like" proteins are derived, with the "C-like" protein arising from initiation at an internal AUG codon (McGinnes et al, 1988). SV5 is therefore seemingly unique among paramyxoviruses in having two mRNAs transcribed from the P gene.…”
Section: Discussionmentioning
confidence: 99%
“…Early peptide mapping data obtained for the P and "C-like" proteins of two other paramyxoviruses, Newcastle disease virus (NDV) and mumps virus, suggested that both proteins are encoded by the same reading frame (Collins et al, 1982;Herrler and Compans, 1982). Recently the NDV and mumps virus P genes have been sequenced and found to contain one open reading frame (Sato et al, 1987;McGinnes et al, 1988;Takeuchi et al, 1988) from which it has been suggested that both the P and "C-like" proteins are derived, with the "C-like" protein arising from initiation at an internal AUG codon (McGinnes et al, 1988). SV5 is therefore seemingly unique among paramyxoviruses in having two mRNAs transcribed from the P gene.…”
Section: Discussionmentioning
confidence: 99%
“…MuV is an enveloped single negative strand RNA virus that belongs to the genus Rubulavirus in the family Paramyxoviridae [1, 2]. MuV particles consist of seven proteins, N, P, M, F, SH, HN and L [3, 4]. V protein, which is encoded by P gene, is a nonstructural protein, and it strongly inhibits interferon (IFN) signal transduction, resulting in shutoff of the IFN-induced host antiviral response [5].…”
Section: Introductionmentioning
confidence: 99%
“…The RNA genome associates with NP to form the helical ribonucleoprotein (RNP), which protects the genome from degradation and serves as the template for RNA synthesis. The NP also associates with the phosphoprotein (P) and indirectly with the large protein (L), in which P and L form the viral RNA-dependent RNA polymerase (vRdRp) (5). The vRdRp uses NP-encapsidated RNA as a template for both replication of the vRNA genome and production of mRNA (2).…”
mentioning
confidence: 99%